THE IMPORTANCE AND PERFORMANCE ANALYSIS OF COMPENSATION IN PT. BANK NEGARA INDONESIA (PERSERO) TBK MAIN BRANCH OFFICE MANADO - Wibisono, Angelia; Lambey, Linda (Universitas Sam Ratulangi, 2016)
The employees are given compensation as a reward and the their right after fulfilling their duties appointed by the company. It is important for the company to continually evaluating the compensation and the importance and performance analysis can be the tool to measure how well the compensation reach the employees. The research aims to analyze the Importance and Performance of Compensation received by the employees of PT. Bank Negara Indonesia (Persero) Tbk, main branch office Manado. This research uses Descriptive Kuantitative method with 100 employees of Bank BNI, resulted in 11 attributes which are the compensation of Bank BNI: Salary, Overtime wage, THR, Bonus and Leave are plotted in quadrant II that indicates a good performance and a high level of importance. Meal Allowance, Severance, and Retirement Fund are plotted in Quadrant I. The respondents attached a high level of importance to these compensation program, yet have a deficient performance. On the other hand, Health Insurance, Uniform and Transportation Allowance are in Quadrant III. They are considered to be not important and have a deficient performance. The management of Bank BNI has to pay a special attention to Meal Allowance, Severance and Retirement Fund and expected to allocate more resources in order to improve those compensation programs. Keywords: compensation, importance and performance analysis